Clustering Tingkat Ekonomi Mahasiswa Calon Penerima Kartu Indonesia Pintar (KIP) Kuliah Metode K-Means - Maimunsuyatni Sompa; Rezqiwati Ishak (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2022)
ABSTRACTThe Smart Indonesia Card (KIP) for Higher Education by the government is under the auspices of theMinistry of Education and Culture. The Smart Indonesia Card (KIP) for Higher Education aims to helpprovide tuition assistance, especially for poor students to continue their studies. It prevents children fromdropping out of education. Universitas Ichsan Gorontalo is one of the private universities granted a quotaof the Smart Indonesia Card (KIP) for Higher Education. The limited number of student admissions (quota)of the Smart Indonesia Card (KIP) for Higher Education requires special attention in determining the rightstudents as recipients on target to get the number of quotas that are not commensurate with the number ofapplicants. In seeing that, clusters are carried out based on the economic level of students to get a groupof students prioritized to get the Smart Indonesia Card (KIP) for Higher Education. The K-Means methodgets clustering results using the Elbow technique, namely 5 clusters. The results of clustering for eachcluster indicate that Cluster 1 is a group of students with medium economic level and taken the secondpriority for recipients of assistance. Cluster 2 is a group of students with low economic levels and becomesthe first priority of recipients of assistance. Cluster 3 is a group of students with middle to high economiclevels and becomes the third priority for recipients of assistance. Cluster 4 is a group of students withmiddle economic level and become the fourth priority for recipients of assistance. Cluster 5 is a group ofstudents with middle to upper economic levels and is the fifth priority for recipients of assistance.Keywords: The Smart Indonesia Card (KIP) for Higher Education, Clustering, Elbow, K-Means